Hollow condensates emerge from gelation-induced spinodal decomposition - Cheng Li; Lingyu Meng; Yongxin Tong; Jie Lin; Zhi Qi (Proceedings of the National Academy of Sciences, 2025)
Recent studies have identified diverse hollow biomolecular condensates, characterized by biomolecule-depleted interiors surrounded by biomolecule-rich shells. Although several formation mechanisms have been proposed, a general thermodynamic driving force remains elusive. Here, we investigate a well-defined system in which the human transcription factor p53 and nonspecific double-stranded DNA (dsDNA) form biomolecule-rich condensates. Introduction of dsDNA containing p53-binding motifs induces a morphological transition to hollow structures, accompanied by a material state transition from liquid-like to gel-like. In vitro assays indicate that the formation of hollow condensates is driven by p21 DNA–induced localized gelation at the condensate periphery. Guided by these findings, we developed a three-component phase-field model that quantitatively recapitulates the formation of hollow condensates. Simulations show that peripheral gelation leads to gradual depletion of protein and Random DNA from the condensate core, triggering spinodal decomposition and lumen formation inside condensates. Together, these results offer mechanistic insights into multicomponent hollow condensates.